Initial Experience Using a High-Definition 3-Dimensional Exoscope System for Microneurosurgery. Issue 4 (29th June 2017) - Sack, Jayson; Steinberg, Jeffrey A; Rennert, Robert C; Hatefi, Dustin; Pannell, Jeffrey S; Levy, Michael; Khalessi, Alexander A
Abstract: BACKGROUND: The operative microscope and endoscope have significantly advanced modern neurosurgery. These devices are nonetheless limited by high costs and suboptimal optics, ergonomics, and maneuverability. A recently developed extracorporeal telescope ("exoscope") operative system combines characteristics from both the operative microscope and endoscope and provides an affordable, portable, high-definition operative experience. Widespread use of exoscopes in neurosurgery has previously been limited by a lack of stereopsis with 2-dimensional(2-D) monitors. OBJECTIVE: To assess the surgical potential of a novel, 3-D, high-definition (4K-HD) exoscope system. METHODS: Assess dissection time and visualization of critical structures in a series of human cadaveric cranial neurosurgical approaches with the 3-D 4K-HD exoscope as compared to a standard operating microscope. RESULTS: Dissection times and visualization of critical structures was comparable with the 3-D 4K-HD exoscope and a standard operating microscope. The low-profile exoscope nonetheless allowed for larger operative corridors, enhanced instrument maneuverability, and less obstruction in passing instrumentation. The large monitor also resulted in an immersive surgical experience, and gave multiple team members the same high-quality view as the primary operator. Finally, the exoscope possessed a more ergonomically favorable setup as compared to the traditional microscope, allowing the surgeon to be in a neutral position despite the operative angle. CONCLUSION: The novel 3-D 4K-HD exoscope system possesses favorable optics, ergonomics, and maneuverability as compared to the traditional operating microscope, with the exoscope's shared surgical view possessing obvious educational and workflow advantages. Further clinical trials are justified to validate this initial cadaveric experience.